2013
DOI: 10.4028/www.scientific.net/amr.690-693.1426
|View full text |Cite
|
Sign up to set email alerts
|

Clean Method for Stickies Control with StickAway Enzyme in ONP Pulps

Abstract: Recovery and use of secondary fiber for paper production is increasing all over the word. In recovered paper recycling, stickies are the most detrimental among the contaminants, affecting both the process efficiency and the quality of the final product. In this study, StickAway enzyme was used to treat the old newspaper(ONP) pulps. The effect of enzymatic treatment on the macro and micro-stickies, the drainage property, as well as the formation of paper products were investigated. After treatment of samples wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The stickies term does not imply any particular chemical composition but is derived from the complex physical and a pioneer in the use of enzymes in process methods [13,15]. Various enzymes (esterases) have been reported that have the ability to degrade components of stickies, preventing agglomeration and its consequences [16][17][18][19]. The number of studies for sticky control using lipases is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The stickies term does not imply any particular chemical composition but is derived from the complex physical and a pioneer in the use of enzymes in process methods [13,15]. Various enzymes (esterases) have been reported that have the ability to degrade components of stickies, preventing agglomeration and its consequences [16][17][18][19]. The number of studies for sticky control using lipases is very limited.…”
Section: Introductionmentioning
confidence: 99%